RANCANG BANGUN MODEL KEBIJAKAN PENGEMBANGAN INDUSTRI RUMAH TANGGA PADA KAWASAN MASYARAKAT MISKIN DI JABODETABEK - Bahtiar Saleh Abbas; Fajar Kurniawan; Nunung Nurhasanah; Achmadi Jayaputra (Puslitbangkesos Kementerian Sosial RI, 2010)
Home Industry is one of the industries that have an important role in achieving a food security in Indonesia. However, in general, the conditions of home industry in Indonesia are still very apprehensive when viewed from the side of capacity, capital and product quality. Based on the Indonesia's home industry problem and high and complex poverty rate, there should be a research that the objective is to develop a model design for the policy on home industrial development on poor region in Greater Jakarta. This research result one major system in designing a policy model for the development of home industry and two subsystems that will support this model in Causal Loop Diagram, created with the help of Power Simulation computer software. This system design has four main variables, namely human resource, economic resource, the growth of home industry and poverty rate. These variables interact with each other.